Is choline kinase alpha a drug target for obesity? - Lacal, Juan Carlos; Ibrahim, Salam A.; Zimmerman, Tahl (Frontiers in Endocrinology, 2024)
Choline kinase alpha (ChoK) is a therapeutic target being developed for a variety of diseases, from cancer to rheumatoid arthritis and from parasites to bacterial infections. Nevertheless, the therapeutic potential of this drug target seems not exhausted and may end up as a possible solution for a larger variety of conditions.Here we present our working model for how ChoK could play a role in obesity and for how drugs being developed as therapeutics for other diseases using ChoK as a target, could be repurposed as prophylactic treatments for obesity. We also present preliminary observations in support of our model.